Acute Lysergic Acid Diethylamide Does Not Influence Reward-Driven Decision Making of C57BL/6 Mice in the Iowa Gambling Task - Lauri V. Elsilä; Nuppu Korhonen; Petri Hyytiä; Esa R. Korpi (Frontiers Media S.A., 2020)
While interest in psychedelic drugs in the fields of psychiatry and neuroscience has re-emerged in recent last decades, the general understanding of the effects of these drugs remains deficient. In particular, there are gaps in knowledge on executive functions and goal-directed behaviors both in humans and in commonly used animal models. The effects of acute doses of psychedelic lysergic acid diethylamide (LSD) on reward-driven decision making were explored using the mouse version of the Iowa Gambling Task. A total of 15 mice were trained to perform in a touch-screen adaptation of the rodent version of the Iowa Gambling Task, after which single acute doses of LSD (0.025, 0.1, 0.2, 0.4 mg/kg), serotonin 2A receptor-selective agonist 25CN-NBOH (1.5 mg/kg), d-amphetamine (2.0 mg/kg), and saline were administered before the trial. 25CN-NBOH and the three lowest doses of LSD showed no statistically significant changes in option selection or in general functioning during the gambling task trials. The highest dose of LSD (0.4 mg/kg) significantly decreased premature responding and increased the omission rate, but had no effect on option selection in comparison with the saline control. Amphetamine significantly decreased the correct responses and premature responding while increasing the omission rate. In conclusion, mice can perform previously learned, reward-driven decision-making tasks while under the acute influence of LSD at a commonly used dose range.